2020
DOI: 10.7150/jca.49266
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Prognostic Index Reflecting Tumor Immune Microenvironment of Lung Adenocarcinoma Based on Metabolism-Related Genes

Abstract: Background: The incidence of lung adenocarcinoma (LUAD) increased substantially in recent years. A systematic investigation of the metabolic genomics pattern is critical to improve the treatment and prognosis of LUAD. This study aimed to analyze the relationship between tumor microenvironment (TME) and metabolism-related genes of LUAD. Methods: The data was extracted from TCGA and GEO datasets. The metabolism-related gene expression profile and the corresponding clinical data of LUAD patients were then integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…With GCH = 149 in “A” but only 3 in “N” and 2 in both “B” and “C”, ENTPD2 is a strong candidate target gene whose manipulation may selectively destroy the primary tumor “A” with practically no effect on the other regions of the prostate. Recent reports considered ENTPD2 relevant for the lung adenocarcinoma [ 71 ] and hepatocellular carcinoma [ 72 ] transcriptomic signatures. Interestingly, expression of ENTPD2 was significantly up-regulated in the nodules “B” ( x = 2.95) and “C” ( x = 2.03) but not in “A” ( x = −1.08).…”
Section: Resultsmentioning
confidence: 99%
“…With GCH = 149 in “A” but only 3 in “N” and 2 in both “B” and “C”, ENTPD2 is a strong candidate target gene whose manipulation may selectively destroy the primary tumor “A” with practically no effect on the other regions of the prostate. Recent reports considered ENTPD2 relevant for the lung adenocarcinoma [ 71 ] and hepatocellular carcinoma [ 72 ] transcriptomic signatures. Interestingly, expression of ENTPD2 was significantly up-regulated in the nodules “B” ( x = 2.95) and “C” ( x = 2.03) but not in “A” ( x = −1.08).…”
Section: Resultsmentioning
confidence: 99%
“…In order to better understand the potential mechanisms of the different prognoses between the high– and low-risk subgroups, GO functional annotation, GSEA, and ssGSEA were performed in the train cohort. First, the package ‘limma’ in R was used to determine the differentially expressed genes (DEGs; |log2FC| >1 and FDR <0.05) between the high– and low-risk subgroups [ 37 ]. Following this, the ‘clusterProfiler’ package in R was used to conduct GO functional annotation of DEGs; meanwhile, GSEA was employed for Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis using the software GSEA 4.0.3 ( http://www.gsea-msigdb.org ) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that MAO-B is overexpressed in lung cancer cells in comparison to normal cells. MAO-B expression increased (mRNA and protein levels) in A549 and H1299 upon ionizing radiation (IR) treatment in a dose-dependent manner [ 61 ]. Therefore, it is concluded that MAO-B can be considered a biomarker for NSCLC and IR resistance.…”
Section: Mao-b’s Role In Cancermentioning
confidence: 99%